Managing reality introduction to the engineering and construction contract - Mitchell, Bronwyn (Institution of Civil Engineers (ICE), 2005)
Managing Reality : Book 1: Introduction to the Engineering and Construction Contract is for those considering using the ECC but need further information, or those who are already using the ECC but need further insight into its rationale. It therefore focuses on the fundamental cultural changes and mind-shift that is required to successfully manage the practicalities of the ECC in use.